Ernestine Wiedenbach’s Prescriptive Theory as Applied to the Management of Appendicitis: A Post Appendectomy Case Study - Nuñez II, Gavino; Merioles, Rommel; Manlongat, Resty May (International Journal of Sustainability and Advanced Integrated Research, 2026)
This case study examined the post-operative nursing management of a 50-year-old male patient diagnosed with ruptured appendicitis with localized abscess, status post appendectomy with lavage of local abscess at Mendero Medical Center, Barangay Pitogo, Consolacion, Cebu. The study aimed to apply Ernestine Wiedenbach’s Prescriptive Theory of Nursing in identifying the patient’s “need-for-help,” implementing appropriate nursing interventions, and validating care outcomes. Gordon’s Functional Health Patterns served as the main assessment instrument. Using a case study design, data were gathered through patient interview, observation, physical assessment, review of laboratory and diagnostic results, nursing care planning, intervention, and outcome evaluation. Findings showed that the patient experienced post-operative pain, risk for infection, impaired mobility, mild dehydration, anxiety, and deficient knowledge regarding post-operative care. Nursing interventions included pain management, aseptic wound care, infection monitoring, assisted ambulation, hydration support, therapeutic communication, spiritual support, family involvement, and discharge teaching using the M.E.T.H.O.D.S. framework. Outcomes showed reduced pain, absence of fever or wound infection, improved ambulation, better coping, and improved understanding of wound care, diet progression, activity restrictions, and warning signs of complications. The study concluded that Wiedenbach’s Prescriptive Theory and Gordon’s Functional Health Patterns supported holistic, individualized, and theory-based post-operative nursing care. The study aligns with SDG 3 – Good Health and Well-Being, SDG 4 – Quality Education, and SDG 17 – Partnerships for the Goals. Its sustainability impact is reflected in safer post-operative recovery, strengthened nursing education, improved institutional care processes, and family-centered continuity of care.
Keywords: Appendectomy; Discharge Teaching; Gordon’s Functional Health Patterns; Post-operative Nursing Care; Prescriptive Theory; Wiedenbach’s Prescriptive Theory